Directorate General of Sea Transportation’s Communication Strategy: Building a Maritime Safety Culture - Riyan Darmawan; Arika Palapa; Winarno, Winarno; Yoga Adiyasa (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study critically investigates the digital communication strategy of Indonesia's Directorate General of Sea Transportation for maritime safety socialization. Employing a multi-method approach involving thematic content analysis of Instagram posts and press releases, in-depth interviews with communication officers, and document analysis of Standard Operating Procedures (SOPs), the research assesses the efficacy of current practices. The findings reveal a system that is highly efficient in procedural, one-way information dissemination, ensuring regulatory accuracy and consistent messaging. However, the study identifies a critical gap between this operational efficiency and the potential for fostering an engaged maritime safety culture. The communication strategy is significantly constrained by rigid SOPs and a risk-averse institutional culture, which prioritizes formal broadcasting over public dialogue and empathetic engagement. Consequently, while functionally robust, the current approach limits opportunities for building the trust and participatory interaction essential for profound behavioral change. The study concludes that transforming Directorate General of Sea Transportation's digital presence from a formal bulletin board into a dynamic community hub requires modernizing communication frameworks with agile protocols and engagement-centric metrics, which is paramount for enhancing maritime safety outcomes in the digital age.